Utopije ljubezni v Cankarjevem romanu Milan in Milena - Leskovec, Andrea (Jezik in slovstvo, 2020)
The subject of this paper is the novel Milan and Milena by Ivan Cankar, which is considered one of the first erotic novels in Slovenian literature. Although Cankar was the first Slovenian writer to problematise the field of sexuality and eroticism in general, the novel has so far not received a detailed analysis in this regard. Therefore, the discussion focuses on the phenomenon of eros, which manifests itself in the novel in all its ambivalence: as the unavailability of the other that leads to infinite lust, and as transgression in the broadest sense of the word.
Keywords: Cankar, Ivan; eros; erotic novel; erotični roman; Slovenian literature; Slovenian writers; slovenska književnost; slovenski pisatelji; transgresija; transgression